Analysis of Bond Rating, Firm Size, Capital Structure and Maturity on Yield to Maturity - Sigit Sanjaya; Hilda Mary (Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of bond rating, firm size, capital structure and maturity on the yield to maturity of corporate bonds listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The type of data in this study uses secondary data. The research population is companies that issue bonds on the IDX. The research sample was selected using the purposive sampling technique. The study results show that: (1) bond rating has a significant effect on bond yield to maturity. (2) firm size has a significant effect on bond yield to maturity. (3) capital structure has a significant effect on bond yield to maturity. (4) maturity has no significant effect on the yield to maturity of bonds. The company is expected to choose the best alternative as a source of funding for the company and on the other hand be able to maintain the balance composition between debt and equity. Investors are expected to be able to choose the best bonds and be able to provide benefits in the future by taking into account the yield to maturity level of bonds.